New source of Fusarium wilt resistance in castor: New source of Fusarium wilt resistance in castor - J JAWAHAR LAL; K ANJANI; M A RAOOF; M SANTHA LAKSHMI PRASAD (Journal of Oilseeds Research, 2020)
Fusarium wilt (Fusarium oxysporum f. sp. ricini) is the major yield limiting biotic factor in castor. The castor germplasm accession RG-1624 was identified as a source of resistance to wilt under artificial epiphytotic conditions at multi locations and confirmed its reaction over years. RG-1624 would serve as a reliable donor for developing wilt resistant cultivars.